The behavior of the lattice parameters in the Bi-Sn-Zn system - Braga Helena M.; Ferreira J.; Malheiros L.F. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Lattice parameters, coefficients of thermal expansion and mass density were determined by means of X-ray powder diffraction between 30 and 180ºC (or 240ºC - depending on samples' composition). Rietveld refinement was performed in order to obtain phases' lattice parameters at each temperature. The Panalytical X' Pert Pro MPD was used for room temperature X-ray diffraction experiments (RTXRD) with bulk samples. The aim was to identify the phases that were present in the sample, as well as, their lattice parameters. For some samples, powder high temperature X-ray diffraction measurements (HT-XRD) were also performed, under a vacuum of 10-5 mbar or an argon atmosphere. It was found that the lattice parameters of (Bi), (Sn) and (Zn) don't change with the composition, at room temperature, as expected since all samples belong to the three phase region. It was also concluded that (Bi) behaves like an isometric crystalline solid on the contrary of (Zn) that has different expansion coefficients for different crystallographic directions a (= b) and c.